Comparative evaluation of salivary and serum CA 15-3 levels in tobacco users with and without potentially malignant oral disorders (PMOD) and oral squamous cell carcinoma (OSCC) - Gopikrishna Padmanabhan; Ramesh kumar; Rajkumar krishnan; Madhu Narayan; R. Ashwini; Shruthi Venkatkumar (Oral Oncology Reports)
Background: The OSCC's prevalence has increased in recent years, which has made it ranked globally as the sixth malignancy and the third-ranked malignancy in Southeast Asia. The biomarker CA 15-3 have been studied in breast carcinoma and might be useful in diagnosing PMODs and OSCC. Aim: This study aims to evaluate & compare the levels of CA 15-3 in tobacco consumers with and without PMODs and OSCC using saliva and serum. Material and methods: Sixty cases were included in the study and were equally distributed among four groups which were the control group, tobacco consumers without PMODs, tobacco consumers with PMODs, and tobacco consumers with OSCC. Serum and saliva were obtained from the patients and were analyzed for CA 15-3 levels using the sandwich ELISA technique. Results: The mean serum CA 15-3 level was higher among subjects in tobacco consumers with OSCC (18.57 ± 4.62) followed by tobacco consumers with PMODs (6.83 ± 1.82), tobacco consumers without PMODs (4.51 ± 0.92) and normal group (2.035 ± 0.32). The mean salivary CA 15-3 level was increased among subjects in tobacco consumers with OSCC (2.025 ± 0.29) followed by tobacco consumers with PMODs (1.21 ± 0.19), tobacco consumers without PMODs (0.58 ± 0.14) and normal group (0.31 ± 0.072). This difference in CA 15-3 level was statistically highly significant among all the groups(p < 0.001). Conclusion: It is concluded that the serum CA 15-3 and salivary CA 15-3 can be a good adjunct in diagnosing OSCC. However, salivary CA 15-3 levels obtained in this study indicated that the saliva can be used as an alternative tool for diagnosis.